Proyecto de factibilidad para la creación de una microempresa de producción de vestidos para bebé y su comercialización en la ciudad de Cuenca - Vivanco Araujo, Mónica Tatiana (2015)
The main objective of this study was to develop a feasibility project for the creation of micro production of baby clothes and marketing in the city of Cuenca, Azuay province corresponding to a business idea or initiative has certain stages of production, marketing, planning and evaluation for the implementation of the company; for which they have taken into account a set of resources, human, material, technological and others that allowed establishing whether the project is viable or not. This work is a representation of a model, bringing together the verbal and graphic information of what the business will have to be, being the synthesis of what the employer will try to organize itself an entrepreneurial work and perform activities necessary and sufficient to have the desired success. With the use of deductive, analytical, mathematical and statistical methods and by applying the techniques of observation and survey has made it to fulfill the main goal which yielded the following results: Market research indicates the annual effective demand for baby clothes and an offer of 525 897 25 052; with an unsatisfied demand 500 845 garments annually, for this marketing plan was raised. The technical report gives a very clear idea of the process of production of baby clothes, indicating an installed capacity serving the 3.16% of the unmet demand, with an annual output of 15,600 garments, which will begin operations using 75 % of installed capacity for the first year with an increase of 5% per year to reach 95% in the year 10. The company will be in Limited Liability Company called "Monica Co. Vivanco. Ltda "with its legal and administrative structure. The study indicates that financial assets of $ 53,145.15 is required, with a cost of $ 175,561.01 for the first year, with revenues of $ 30,218.44. The breakeven point for the first year is 52.51% of installed capacity and $ 119,853.41 for the first year. The financial evaluation that assesses the company globally, yielded information on the financial suitability of the project; so we have a positive NPV of 175,931.40; IRR, has a percentage of 67.36%; the benefit cost ratio is greater than one with a profit of 0.30 cents for every dollar invested. The PR / C is 1 year, 6 months and 12 days; in addition it was found that the project has a sensitivity of 99% with increasing costs of 19.85% and a decrease in revenue of 12.40%